anonymous
  • anonymous
Can someone help me to solve the already intergrated problem so I can compare my answer absolute (6t - 3t^2) from x = 1 to x=0 + absolute (6t -3t^2) from x= 5 to x= 1
Mathematics
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
don't you mean from x=0 to x=2 and negative integral from x=2 to x=5 ... because the formula crosses x-axis at x=2.
anonymous
  • anonymous
we got 6t-3t^3... integrating reveals: 3t^2-t^3. from x=0-2 4 from x= 2-5 -54 total area between graph and x-axis : 58

Looking for something else?

Not the answer you are looking for? Search for more explanations.